Pengaruh Pengetahuan Investasi dan Motivasi Investasi Terhadap Minat Investasi di Pasar Modal - Indrayani Indrayani (Journal of Trends Economics and Accounting Research, 2023)
The capital market is a means of connecting business actors who need funds and people who have excess funds to invest. Researchers see that public interest, especially students, to invest is still very low even though students should be a part of society that has a lot of opportunities and has the potential to become investors in the capital market for the future. So that researchers are interested in studying the effect of investment knowledge and investment motivation as independent variables on student investment interest as the dependent variable. The data used in this study is primary data derived from responses to questionnaires which were distributed to 100 respondents who are students of the Faculty of Economics and Islamic Business (FEBI) IAIN Parepare who are the objects of this research. The method used in this study is descriptive quantitative, where data testing uses the SPSS 26 application. The classic assumption tests used are the normality test, multicollinearity test, and heteroscedasticity test. Meanwhile, to test the hypothesis used correlation coefficient test (R), test the coefficient of determination (R2), partial test (t-test) and simultaneous test (F-test). Based on the results of the analysis carried out, it was concluded that both investment knowledge and investment motivation significantly influence the investment interest of FEBI IAIN Parepare students.